Design of a Predictive Model for Prospective New Students Using Monte Carlo Simulation - Paramita, Dela; Efriyanti, Liza; Zakir, Supratman; Imamuddin, M. (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The competition between universities in the admission of new students is becoming increasingly intense, making it more difficult for the public, especially prospective students, to choose a study program. The Department of Hadith Sciences at UIN Syech M. Djamil Djambek Bukittinggi has fewer applicants compared to other departments due to the limited interest of prospective students in enrolling. In response to this issue, the author developed a Monte Carlo simulation predictive model that allows prospective students to estimate the number of applicants to the Department of Hadith Sciences for the upcoming academic year. The research technique employed in this study uses Monte Carlo simulation to apply this research. The number of students in the Department of Hadith Sciences who enrolled from 2019 to 2023 serves as the data used to predict the number of new student registrations. The accuracy of the simulation in estimating the number of new students who will enroll in the Department of Hadith Sciences is 218 students, with an average annual accuracy of 65.1%. By applying the Monte Carlo method, it is possible to predict the number of students who will enroll in the Department of Hadith Sciences with a relatively high level of accuracy in its application